The Pauline Epistles in Arabic : Manuscripts, Versions, and Transmission - Zaki, Vevian, (Biblia Arabica ;, 2021)
In this study, Vevian Zaki places the Arabic versions of the Pauline Epistles in their historical context, exploring when, where, and how they were produced, transmitted, understood, and adapted among Eastern Christian communities across the centuries. She also considers the transmission and use of these texts among Muslim polemicists, as well as European missionaries and scholars. Underpinning the study is a close investigation of the manuscripts and a critical examination of their variant readings. The work concludes with a case study: an edition and translation of the Epistle to the Philippians from manuscripts London, BL, Or. 8612 and Vatican, BAV, Ar. 13; a comparison of the translation strategies employed in these two versions; and an investigation of the possible relations between them.